Lost in Translation: Unified Consumption Theory, Dynamic AS-AD, and Business Cycles - Max Gillman (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
The paper shows how aggregate AS-AD can be derived within the standard neoclassical dynamic setting known as the Ramsey-Cass- Koopmans (RCK) model. AS-AD is the stationary equilibrium of the deterministic dynamic general equilibrium framework. The derivation builds a permanent income type consumption demand that corresponds to a consumption theory that depends on current income, illustrating analytically how to unify the alternative theories within RCK. With permanent income de.ned by the flow on time and goods endowments, the logic of changing both endowments simultaneously coincides with changing the external labor margin along with goods sector productivity in order to explain business cycles. This gives rise to a stylistic AS-AD explanation of the business cycle that is consistent with the primary features of the RBC literature and consumption theory.
Keywords: A22; A23; E13; 330; Ramsey-Cass-Koopmans; supply; demand; state variable; external labor margin; Konsumtheorie; Angebot; Nachfrage; Dynamisches Gleichgewicht; Konjunkturtheorie